Social Perception and Emotional Deprivation For Preparatory Stage Students - Asil, pilsam Aoad (Al-Adab Journal, 2018)
The research objectives are conducted to the following :1- To know the level of Social Perception for Preparatory stage students 2- To know the level of Emotional Deprivation for Preparatory stage students 3-To know the relationship between the Social Perception and Emotional Deprivation for Preparatory stage students. The current research has determined sample of Preparatory forth stage students (scientific and literary) for both males and females in Baghdad (morning studies) for 2016-2017. Theoretical frameThis research viewed several adoptes in The research procedures results Building Adopting Social Perception scale1- (Atwan2015) and Adopting Cognitive Failure scale(Al-Saadi2016) after assures its truthes and stability on its articles2-The two mentioned measures were applied at the same time on sample educational counselors (160) students male and female students during 25-28/2/2017 .the researcher used the following . Data had been analyzed with help of statistic programs for social sciences in data process (SPSS)As a result, it had been reached to results listed below1- The research results showed that the Preparatory stage studentsadopted Social Perception2-results showed that the Preparatory stage students do not suffer from emotional deprivation3-Results showed that there is nigtive connection relationship between for Preparatory stage male and female students Social Perception and Emotional DeprivationThe researcher submitted some recommendations and suggestions.